2019
DOI: 10.1111/rda.13397
|View full text |Cite
|
Sign up to set email alerts
|

Function of berberine on porcine in vitro fertilization embryo development and differential expression analysis of microRNAs

Abstract: Contents The effect of berberine (Ber) on in vitro fertilization (IVF) embryo development in pigs and the associated differential expression of microRNAs (miRNAs) in the embryo were investigated. NCSU‐23 embryonic culture medium was used for a control group, while NCSU‐23 embryonic culture medium added with Ber was used for a Ber group. The embryo development rates in these groups were determined, and the zygotes, 4‐ and 8‐cell embryos, and blastocysts were collected for cDNA microarray analysis. The developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In keeping with zebrafish results, a small number of studies in rodents, in vivo and in vitro, using various modalities of administration, showed that BRB may exert toxic and teratogenic effects during development [18][19][20][21] . On the other hand, discrepancies between our results and those indicating the lack of toxic and/or teratogenic effects of BRB during development [25][26][27] could be due, at least in part, to the different experimental model, concentration/dose and route of administration of the compound, confirming previous observations 6 .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In keeping with zebrafish results, a small number of studies in rodents, in vivo and in vitro, using various modalities of administration, showed that BRB may exert toxic and teratogenic effects during development [18][19][20][21] . On the other hand, discrepancies between our results and those indicating the lack of toxic and/or teratogenic effects of BRB during development [25][26][27] could be due, at least in part, to the different experimental model, concentration/dose and route of administration of the compound, confirming previous observations 6 .…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, Ali and colleagues showed that addition of BRB to the culturing medium of zebrafish embryos from 24 h post-fertilization (hpf) to 120 hpf resulted in increased mortality rate in a time- and concentration-dependent manner, and in phenotypic abnormalities, such as uninflated swim bladder, yolk sac edema and pericardial edema, in a concentration-dependent manner 22 24 . On the other hand, other works indicated that BRB did not induce developmental toxicity, as previously shown in vitro in mouse 25 and porcine early embryos 26 . In this line, BRB increased clinical pregnancy rate and promoted the survival away from the nest following the transplantation of in vitro developed early mouse embryos 25 and continuous intragastric administration of Chinese Goldthread rhizome decoction, which contains BRB, or pure BRB to pregnant rats and mice did not cause abortion and developmental toxicity 27 .…”
Section: Introductionmentioning
confidence: 56%
“…In order to study the effects of Ber and miR‐192 on embryo development of IVF, fresh semen from the boar was heated for 30 min using a water bath at 37°C, then centrifuged (1,000 r/min, 5 min). Concentrated semen was transferred to capacitated fluid (Wang et al., 2019) and incubated for 30 min at 39°C under 5% CO 2 . Oocytes with the first polar body were transferred to 50‐μl mTBM fertiliser droplets for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrated semen was transferred to capacitated fluid (Wang et al, 2019) and incubated for 30 min at 39°C under 5% CO 2 . Oocytes with the first polar body were transferred to 50μl mTBM fertiliser droplets for 30 min.…”
Section: Ivf Of Porcine Oocytesmentioning
confidence: 99%
“…One exception is for berberine that was shown to promote angiogenesis directly through miR-29b upregulation, upon induction of ischemia in mice [174]. The rest of the available data is restricted to experiments analyzing alkaloids as effectors of miR induction in different animal or cell models; for example, a recent study analyzed miRNA induction by berberine in porcine embryos [175]. Similarly, a berberine-containing commercially prepared traditional Chinese medicine Huang-Lian-Jiee-Dwu-Tang [176] was shown to induce VEGF and miR-126 expression in mesenchymal stem cell exosomes [177].…”
Section: Plant-based Alkaloidsmentioning
confidence: 99%